Cysteine preservation confers resistance to glutathione-depleted cells against ferroptosis via CDGSH iron sulphur domain-containing proteins (CISDs). (2nd June 2020) - Homma, Takujiro; Kobayashi, Sho; Fujii, Junichi
Abstract: Ferroptosis is a type of iron-dependent, non-apoptotic cell death, which is typically induced by the suppression of phospholipid hydroperoxide-glutathione peroxidase (GPX4) activity and a corresponding elevation in lipid peroxidation products. While the inhibition of the xCT-mediated uptake of cystine commonly causes ferroptosis, the sensitivity of cells to the inhibition of the glutathione (GSH) synthesis by buthionine sulfoximine (BSO) varies considerably. The objective of this study was to clarify the underlying mechanism responsible for these differential responses to the targeted inhibition of either the cysteine (Cys) supply to or GSH synthesis in the cells. While intracellular GSH levels were depleted when mouse hepatoma Hepa 1-6 cells were treated with BSO, intracellular Cys levels rather increased and viability of the cells remained unchanged, suggesting that Cys has a role in this resistance to ferroptosis under conditions of GSH depletion. When the cells were treated with pioglitazone (PGZ), a potent inhibitor of CDGSH iron sulphur domain-containing proteins (CISDs), PGZ alone had no effect on either cell viability or GSH levels but induced ferroptosis under conditions of GSH depletion by the BSO treatment. In the case of the co-treatment with PGZ and BSO, ferrous iron and the levels of lipid peroxides were robustly increased in the cells, but neither endoplasmic reticulum stress nor apoptosis was evident. Collectively, CISDs appeared to exert an anti-ferroptotic function by suppressing free iron toxicity and the subsequent lipid peroxidation with assistance provided by Cys.